Stress-induced intrachromosomal recombination in plant somatic cells. - Lebel, E G (1993)
Levels of induced homologous recombination between chromosomal repeats in plant somatic cells were examined. Transgenic plants of Nicotiana tabacum hemi- or homozygous for pairs of deletion derivatives of the neomycin phosphotransferase (nptII) marker gene integrated at a single genomic locus were produced. Homologous recombination within the overlapping parts of the nptII gene restored the function and the resulting kanamycin resistance was used for scoring recombination frequency. The recombination events were confirmed by the appearance of a characteristic 1245-base-pair EcoRV fragment detected in all kanamycin-resistant clones tested. The rate of spontaneous recombination was found to be related to the copy number of recombination substrates and was 9 x 10(-5) and 19 x 10(-5) for hemi- and homozygote strains, respectively. Ionizing radiation, mitomycin C, and heat shock markedly increased the frequency of intrachromosomal recombination. Low doses of x-rays (1.25 Gy) enhanced the relative recombination frequency to approximately twice the spontaneous value. The presence of mitomycin C increased the frequency of recombination 9-fold and exposure to an elevated temperature (50 degrees C) increased it 6.5-fold. The x-ray and heat shock treatments reduced cell viability to 53% and 8%, respectively. Mitomycin C treatment had no effect on cell survival.